Interoception: Current Knowledge Gaps and Future Directions in Neuroscience, Psychopathology, and Clinical Applications - Leão, Larissa Medeiros Maia; Meneses Rêgo, Amalia Cinthia; Araújo-Filho, Irami (International Journal of Innovative Research in Medical Science, 2025)
Interoception, the process by which the nervous system senses, interprets, and regulates internal bodily states, is fundamental in maintaining physiological homeostasis, emotional regulation, and cognitive processing. Despite its significance, significant knowledge gaps persist regarding their underlying neural mechanisms, contributions to psychiatric and neurological disorders, methodological limitations in assessment, and potential clinical applications. This review synthesizes current findings and highlights unresolved questions in interoceptive research. The insular cortex, anterior cingulate cortex, brainstem, and autonomic nervous system are integral to interoceptive processing, yet the precise functional interactions among these regions remain unclear. Disruptions in interoceptive signaling have been implicated in psychiatric conditions such as anxiety, depression, schizophrenia, and autism spectrum disorder, as well as neurodegenerative diseases including Parkinson’s and Alzheimer’s. However, whether these interoceptive alterations are causative or consequential remains an open question. Inconsistencies in interoception assessment methods hinder progress, necessitating standardized, multimodal approaches that integrate behavioral, physiological, and computational metrics. Emerging evidence supports the clinical potential of interoception-based interventions, including mindfulness, vagus nerve stimulation, biofeedback, and cognitive behavioral therapy. Yet, their mechanisms of action and efficacy across diverse populations require further investigation. Advances in artificial intelligence and predictive modeling may enhance diagnostic precision and personalized treatment strategies. By addressing these challenges, future research can deepen our understanding of interoception’s role in health and disease, ultimately informing innovative therapeutic approaches.